Evaluation of National Resident Matching Program and Electronic Residency Application Service Data in the Integrated Plastic Surgery Match. Issue 5 (June 2021) - Gallegos, Jose; Raghava, Narayan; Inglesby, Dani C.; Zlomke, Haley A. L.; Young, Zachary T.; Herrera, Fernando A.
Abstract : Introduction: The National Resident Matching Program and Electronic Residency Application Service provide data for tracking trends among applicants in each specialty over the past 5 years. The purpose of this study was to examine this information and determine sex and race/ethnicity distribution over the past 5 years. Methods: The National Resident Matching Program and Electronic Residency Application Service databases were surveyed for trends in the following categories: number of positions, number of applicants, percent of applicants per position, and number of applicants by sex and self-identified race/ethnicity. This information was analyzed graphically for visual representation of the changes in the field. Results: While there has been a steady increase in number of positions offered, there has also been a significant decrease in number of applicants, resulting in an increase in number of positions offered per applicant. While female and Asian applicants have increased in number, rates of applications from other diverse groups have remained stagnant. Conclusions: The number of plastic surgery positions offered has increased, whereas the number of applicants has decreased, resulting in a reduction in the number of applicants per position. Lack of racial diversity remains a significant issue in the applicant pool.